Jerónimo Martins- return after Covid-19/getting to know the changes in the market and the online channels - Esteves, Rafaela Aguiar (2022)
Jerónimo Martins operates in the retail and food distribution sectors in Portugal, Poland and Colombia. Share Capital is over 629 million euros, listed in the Euronext Lisbon Stock Exchange and is present in the PSI20 index. The analysis is based on the development and expansion of the business, with a comparison and relationship between the company, the market, and the peers. The methods used are the DCF and Multiples Valuation. Thus, it was possible to arrive at a share price in December 2022 of 23,41€, associated with a total return for the investor of 18,33% resulting in a buy position.